PENANGANAN PERMASALAHAN KAUM MUDA DALAM BUDAYA POPULISME MASYARAKAT URBAN - Sholikhah, Linda Dwi; Hayat, Saeful (JPW (Jurnal Politik Walisongo), 2019)
Young people are those who are so easily influenced by modern and primitive trends. They are a group of people who are quickly touched by change. The development felt fast in the city. Culture of young people who follow the modern trend needs supervision and guidance so as not to fall into the negative direction or even erode the identity of the nation. In its development the people should have opportunities in social life and an active role in government. However, in its development there are several problems that arise so that proper handling of self, family and school environment, and government is needed. This is done to improve the youth activism as the next generation of nation that is expected to bring this country more prosperous and prosperous.